MG-123 Exonic and intronic NRXN1 deletions: Novel genotype-phenotype correlations. (4th December 2015) - Lowther, Chelsea; Speevak, Marsha; Armour, Christine; Goh, Elaine; Graham, Gail; Li, Chumei; Zeesman, Susan; Nowaczyk, Malgorzata JM; Schultz, Lee-Anne; Morra, Antonella; Nicolson, Robert; Rajguru, Manjulata; et al.
Abstract : Objectives: To 1) further characterise the extended phenotype of exonic NRXN1 deletions and 2) systematically evaluate the pathogenicity of intronic NRXN1 deletions in order to help inform clinical diagnostic practice. Methods: We examined clinically ascertained cases from three Canadian cytogenetic laboratories for exonic NRXN1 deletions. Referring physicians completed a clinical checklist to identify major lifetime features and illnesses. One lab's clinically referred cases were available to investigate the prevalence of intronic NRXN1 deletions in comparison to 15, 254 controls. Genome-wide CNV data from high-resolution microarrays were investigated for the presence of additional rare variants. Results: We identified 41 (0.21%) exonic NRXN1 deletions among 19, 263 clinically referred cases, an over eight-fold increase compared to controls (p < 0.0001). Novel phenotypes identified in two or more exonic NRXN1 deletion cases included nine adults with comorbid intellectual disability and a psychiatric illness, movement disorders, automutilation, sleep disorders, and obsessions and preoccupations. The prevalence of congenital anomalies was low. The prevalence of intronic NRXN1 deletions did not differ between clinical cases (19/6, 022; 0.32%) and controls (55/15, 524; 0.35%). Additional pathogenic rare variants were four times more common in intronic (n = 6/19; 31.6%) compared to exonic (n = 3/41; 7.3%) NRXN1 deletion cases. Conclusions: The expression of exonic NRXN1 deletions is primarily neuropsychiatric and may be associated with comorbid intellectual disability and a psychiatric illness in adulthood. To our knowledge this is the first study to demonstrate that the majority of intronic NRXN1 deletions by themselves are unlikely to cause clinical phenotypes, however further study on their potential functional impact is needed.